2023
DOI: 10.1093/jjco/hyad090
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative plasma D-dimer level was an independent prognostic factor for patients with PDAC after curative resection: a retrospective analysis

Li Zhifei,
Liang Yuexiang,
Chang Shaofei
et al.

Abstract: Objective In this study, the relationship between preoperative plasma D-dimer level and overall survival and recurrence free survival were evaluated in patients with curative resection of pancreatic ductal adenocarcinoma. Methods Preoperative plasma D-dimer level of 573 patients with pancreatic ductal adenocarcinoma were collected. The univariate and multivariate Cox hazard models were used to identify independent variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…23 Moreover, elevated preoperative DD level could independently predict major complications and act as an independent prognostic factor for overall survival and recurrence free survival in patients with malignant diseases. [24][25][26] Previous studies also suggested that increased DD value was observed in virus and tuberculosis infected patients and was associated with the severity of diseases. 27,28 However, the relationship between DD and treatment outcomes in inflammatory diseases remains to be further explored.…”
mentioning
confidence: 95%
“…23 Moreover, elevated preoperative DD level could independently predict major complications and act as an independent prognostic factor for overall survival and recurrence free survival in patients with malignant diseases. [24][25][26] Previous studies also suggested that increased DD value was observed in virus and tuberculosis infected patients and was associated with the severity of diseases. 27,28 However, the relationship between DD and treatment outcomes in inflammatory diseases remains to be further explored.…”
mentioning
confidence: 95%